Method for in-situ synthesis of metal organic frameworks (MOF's), covalent organic frameworks (COF's) and zeolite imidazolate frameworks (ZIF's), and applications thereof
Patent Information
- Application Number
- JP2024206635
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-03-14
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 2025023049000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to methods for the in situ synthesis of classes of compounds known as MOFs (metal-organic frameworks), COFs (covalent organic frameworks) and ZIFs (zeolitic imidazolate frameworks) in and on different types of substrates, as well as to the use of such substrates with in situ synthesized MOFs, COFs and ZIFs. The present invention also relates to adsorbent matrices / substrates containing in situ synthesized or impregnated MOFs, COFs and ZIFs, as well as to the use of such adsorbent matrices / substrates.
[0002] Over the last century, zeolitic materials, silica gel and / or insoluble metal silicates, as well as activated alumina, activated carbon, primarily inorganic materials, have remained the go-to materials of choice in adsorption applications, such as gas masks, dehumidification and humidity control, water softening using ion exchange processes, chromatography, adsorption chillers, and catalysis, due to their versatility.
[0003] Zeolites are known to be synthesized for such applications by mixing aqueous solutions of alumina or aluminates and silica in a basic medium at elevated temperatures. The aluminosilicate gel so formed undergoes hydrothermal crystallization at specific times, temperatures, and pressures. Insoluble metal silicates are usually prepared by mixing water glass with an aqueous solution of a divalent or trivalent metal salt at specific temperatures and times, followed by washing of unreacted / excess starting materials or by-products formed during the reaction. Silica gels are typically prepared by mixing water glass with an acid, thus forming a gel, followed by drying, washing, and drying again. It is also known in the art to prepare metal silicates and silica gels in situ on substrates shaped like honeycombs. While these remain the mainstay of materials used in dehumidification and other adsorption-based applications, there has been progress in the development of alternative materials that can replace and / or complement them. In recent decades, and more specifically in the past decade, a new set of classes of adsorption materials with organic linkers / ligands as key substructures have been extensively investigated, which are called MOFs, COFs, and ZIFs. Some of these materials are promising for dehumidification and other adsorption applications for CO2, VOCs, and other gases due to properties such as high surface area, potentially high adsorbent uptake, and / or regeneration at low temperatures.
[0004] Materials such as metal-organic frameworks, covalent organic frameworks, and zeolitic imidazolate frameworks are an emerging class of materials with a wide range of industrial applications, e.g., in gas separation membranes, energy storage devices, biodegradable filters, catalytic filters, gas storage devices, moisture adsorption, carbon capture, carbon capture, gas capture, bioalcohol capture, drug delivery, etc. These materials hold some promise in such applications due to their unique structural and chemical properties, and furthermore, can be relatively easily tuned or customized for specific applications.
[0005] Prior art and patents on MOFs, COFs, and ZIFs are discussed below. Briefly, they are all within the category of well-known wet and dry chemical synthesis methods. Such methods of material preparation require the use of complex mechanisms and processes. Furthermore, after the material is prepared, it becomes necessary to utilize binders, etc. in coating, granulation, etc., which hinders its sufficient performance in certain applications as well as the form in which it can be utilized. For example, the use of binders may hinder the actual performance / capability of the material in certain applications.
[0006] The novel method of the present invention is based on in situ synthesis, which opens the possibility of being used in existing and new applications requiring exposure of high surface exchange areas, as well as new materials that provide same, and also eliminates / minimizes the reliance on binders to bond the material to the substrate. Furthermore, substrates of certain shapes traditionally require the use of adhesives to bond multiple layers of the substrate. In one embodiment, the method of the present invention in certain cases provides an in situ synthesized material that itself performs this function. [Background technology]
[0007] Metal-organic frameworks are nanoporous, crystalline, and synthetic materials consisting of metal ions / clusters coordinated to organic molecules to form one-, two-, or three-dimensional structures with large surface areas. The choice of metal and linker has significant effects on the structure and properties of MOFs. The manipulations possible in synthesis, structure, availability of coordination sites on the metal, high porosity, high surface area, and good flexibility of the structure are of great interest. MOFs are an exciting development in nanotechnology that has emerged in the past decade. They exhibit unique properties and have the potential to expand the market for nanoporous materials. They have potential in high value applications such as natural gas storage, processing, carbon capture, catalysis, etc. They have a high potential for moisture adsorption for cooling applications compared to conventional desiccants. MOFs can replace silica gel type adsorbents used in adsorption cooling systems that are subject to size, performance, and cost limitations.
[0008] Certain MOFs exhibit significant natural gas storage capabilities even at low pressures. A significant market barrier to natural gas storage is the current need for storage and refueling at extremely high pressures. MOFs have the potential to become an important technology in natural gas storage and processing. Such MOFs may be designed / modified to be selective about the gases they capture. Many MOFs offer significant opportunities for biological and medical applications.
[0009] MOFs are typically prepared by mixing organic ligands / linkers and metals / metal salts with or without a solvent, and then subjecting the mixture to specific conditions of temperature and time, and if necessary pressure and / or agitation to obtain the MOF, followed by optional filtration, washing and drying.
[0010] MOFs known in the art include MOF-5, Cu-BTC, MIL-53, MIL-68, MIL-100(Fe), Mg-MOF-74, MIL-101(Cr), MOF 801, MOF 177, CAU-10H, MOF 808, IR-MOF-8, CPO-Ni(27), aluminum fumarate, MOF 199, DMOF(Zn), DUT-4, and the like.
[0011] The bidentate and tridentate organic compounds are oxalic acid, tartaric acid, succinic acid, 1,4-butanedicarboxylic acid, 1,4-butene-dicarboxylic acid, 4-oxopyran-2,6-dicarboxylic acid, decanedicarboxylic acid, 1,8-heptadecanedicarboxylic acid, 1,6-hexanedicarboxylic acid, heptadecanedicarboxylic acid, acetylenedicarboxylic acid, 1,9-heptadecanedicarboxylic acid, 1,2-benzenedicarboxylic acid, 1,3-benzenedicarboxylic acid, 2,3-pyridinecarboxylic acid, pyridine-2,3-dicarboxylic acid, 1,4-benzenedicarboxylic acid, p-benzenedicarboxylic acid, imidazole-2,4-dicarboxylic acid, 2-methylquinoline-3,4-dicarboxylic acid, quinoline-2 ,4-dicarboxylic acid, quinoxaline-2,3-dicarboxylic acid, 6-chloroquinoxaline-2,3-dicarboxylic acid, 1,3-butadiene-1,4-dicarboxylic acid, 4,4'-diaminophenylmethane-3,3'-dicarboxylic acid, quinoline-3,4-dicarboxylic acid, diimidedicarboxylic acid, pyridine-2,6-dicarboxylic acid, 2-methylimidazole-4,5-dicarboxylic acid, 7-chloro-4-hydroxyquinoline-2,8-dicarboxylic acid, thiophene-3,4-dicarboxylic acid, tetrahydropyran-4,4-dicarboxylic acid, perylene-3,9-dicarboxylic acid, 2-isopropylimidazole-4,5-dicarboxylic acid, perylene dicarboxylic acid, Pluriol E 200-dicarboxylic acid, 3,5-cyclohexadiene-1,2-dicarboxylic acid, octane dicarboxylic acid, pentane-3,3-carboxylic acid, 3,6-dioxaoctane dicarboxylic acid, 4,4'-diamino-1,1'-biphenyl-3,3'-dicarboxylic acid, 4,4'-diaminobiphenyl-3,3'-dicarboxylic acid, benzidine-3,3'-dicarboxylic acid, 1,1'-binaphthyl dicarboxylic acid, 1,4-bis(phenylamino)benzene-2,5-dicarboxylic acid, 7-chloro-8-methylquinoline-2,3-dicarboxylic acid, 1-anilinoanthraquinone-2,4'-dicarboxylic acid, 1,4-bis(carboxymethyl)piperazine-2,3-dicarboxylic acid, phenylinanedicarboxylic acid, 7-chloroquinoline-3,8-dicarboxylic acid, polytetrahydrofuran 250-dicarboxylic acid, 1-(4-carboxy)phenyl-3-(4-chloro)phenylpyrazoline-4,5-dicarboxylic acid, 1,4,5,6,7,7-hexachloro-5-norbornene-2,3-dicarboxylic acid, 1,3-dibenzyl-2-oxoimidazolidine-4,5-dicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, naphthalene-1,8-dicarboxylic acid, 1,3-dibenzyl-2-oxoimidazolidine-4,5-cis-dicarboxylic acid, 2,2'-biquinoline-4,4'-dicarboxylic acid, 2-benzoylbenzene-1,3-dicarboxylic acid, pyridine-3,4 dicarboxylic acid, 3,6,9-trioxaundecane dicarboxylic acid, Pluriol E 300 dicarboxylic acid, Pluriol E 400 dicarboxylic acid, hydroxybenzophenone dicarboxylic acid, Pluriol E 600-dicarboxylic acid, pyrazole-3,4-dicarboxylic acid, bis(4-aminophenyl)sulfondiimide-dicarboxylic acid, 5,6-dimethyl-2,3-pyrazinedicarboxylic acid, bis(4-aminophenyl)etherdiimide-dicarboxylic acid, 2,3-pyrazinedicarboxylic acid, 4,4'-diaminodiphenylmethanediimide-dicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,3-adamantanedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 8-methoxy-2,3-naphthalenedicarboxylic acid, 8-sulfo-2,3-naphthalenedicarboxylic acid , anthracene-2,3-dicarboxylic acid, 8-nitro-2,3-naphthalenecarboxylic acid, 2',3'-diphenyl-p-terphenyl-4,4''-dicarboxylic acid, (diphenyl ether)-4,4'-dicarboxylic acid, 4(1H)-oxothiochromene-2,8-dicarboxylic acid, imidazole-4,5-dicarboxylic acid, 5-tert-butyl-1,3-benzenedicarboxylic acid, 7,8-quinolinedicarboxylic acid, 4,5-imidazoledicarboxylic acid, etc., or 1,3,5-benzenetricarboxylic acid, 1,3,5-tris(4-carboxyphenyl)benzene, etc., can be derived from dicarboxylic acids.
[0012] Excess solvent residue, unwanted starting materials, and / or unwanted by-products can be removed by methods such as washing the filtrate one or more times and drying.
[0013] The above exemplified MOFs have applications across various industries such as sustainable drug release or moisture adsorption at different RH from low to high RH, heterogeneous catalysis, natural gas storage, dispersive solid phase extraction, fluoride ion removal, sustained release and product separation applications, and heat exchange applications, various adsorption applications for hydrogen sulfide gas, methane gas, etc., and as adsorbents for heat pump applications.
[0014] Zeolitic imidazolate frameworks (ZIFs) are a group of metal-organic frameworks that are topologically isomorphous with zeolites. ZIFs are composed of tetrahedrally coordinated transition metal ions (e.g., Fe, Co, Cu, Zn) connected by imidazolate linkers, where the metal-imidazole-metal angle is 145°. Also, in the case of zeolites, the Si-O-Si angle is 145°, and ZIFs have a zeolite-like topology. They are a subset of MOF hybrids, since they combine organic and metal frameworks. As a result, hybrid microporous and crystalline structures are created. The properties of MOF / ZIFs depend largely on the properties of the metal clusters, the ligands / linkers, and the conditions maintained during their formation. ZIFs have significant properties that are applied, for example, in carbon capture processes, methane capture, nitrogen-methane separation, hydrogen production, etc. To change the carbon dioxide adsorption capacity of ZIFs, functional groups with different polarities / symmetries can be employed on the imidazolate ligands without changing the transition metal cation. ZIFs are generally more thermally and chemically stable than MOFs and therefore may be suitable for use in a wide range of temperatures and chemical processes. ZIFs exhibit hydrophobicity and water stability. Zeolites and MOFs adsorb water along with CO2. Water vapor is usually present in carbon-rich exhaust gases, and MOFs adsorb water, lowering the amount of CO2 required to reach saturation. ZIFs perform nearly identically in dry and wet conditions. They have high CO2 selectivity over water, which allows ZIFs to store more carbon before reaching saturation. Due to their robust porosity, chemical stability, and resistance to thermal changes, ZIFs such as ZIF-1, ZIF-7, ZIF-8, ZIF-35, ZIF-67, ZIF-69, ZIF-71, ZIF-90, ZIF-95, and ZIF-100 have been investigated for a variety of applications such as gas storage, carbon capture, bioalcohol capture, gas separation, CO2 and N2 and methane separation. Many ZIFs have also been investigated for their use in drug delivery, catalysis, sensing applications, and applications requiring hydrophobic and / or hydrophilic properties.
[0015] Covalent organic frameworks (COFs) are two- or three-dimensional porous crystalline organic solids made from light elements such as C, B, N, H, and O. They are extended structures in which the building blocks are linked by strong covalent bonds. They possess rigid structures, low density, and high thermal stability up to 600°C. Preparation of COFs involves constructing molecular blocks that can be functionalized into lightweight materials for various applications. Illustrative examples of COFs include COF-202, COF-1, COF-5, PcPBBA, TpPa-1, TpPa-2, TpPa-NO2, TpPa-F4, TpBD, TpBD-(NO2), etc., all of which have applications in industries such as gas storage, sensing, catalysis, and optoelectronics. COFs typically exhibit persistent porosity and specific surface areas that exceed those of most zeolites and porous silicates, which is why COFs have potential use in applications such as carbon capture, hydrogen storage, catalysis, methane storage, gas separation and dehydration, and / or gas / moisture adsorption applications. These properties make COFs good candidates to replace metal silicates, zeolites, and silica gels in a variety of applications.
[0016] Literature exists in the art for preparing such MOFs, COFs, and ZIFs. Conventional techniques for preparing MOFs typically follow one of the following approaches: wet methods, dry methods, microwave-mediated methods, and spray methods.
[0017] Wet methods for preparing MOFs involve either hydrothermal or solvothermal techniques and typically involve first forming a solution of an organic ligand in water or any other solvent. This is then reacted with a metal salt solution for a specific time and temperature. The resulting product is then washed with water or a solvent, as desired, to obtain the required metal-organic framework (MOF).
[0018] Dry methods of MOF formation involve the use of mechanochemical techniques where the use of water or solvents is substantially avoided. The reaction is carried out in substantially dry conditions, usually using an extruder. Apparently, this method is limited to MOFs and has limited extension to COFs and ZIFs.
[0019] Microwave-mediated methods usually involve converting stock solutions of metal-organic framework precursors into reaction solutions, followed by exposure to microwave irradiation. MW irradiation is used as the reaction igniter, and the resulting MOFs are withdrawn from the reactor. This can also be used to prepare covalent organic frameworks and zeolitic imidazolate frameworks using stock solutions of the respective precursors. However, one obvious limitation of this technique is its very energy-intensive nature, as it is entirely dependent on microwave generation.
[0020] The spraying methods previously known only for producing MOFs usually involve sequential or simultaneous spraying of precursor solutions onto the surface to be coated such that MOFs are formed on the surface, which may not be entirely suitable for producing COFs or ZIFs.
[0021] Examples of wet method preparations of MOFs include: 1. Preparation of MIL-100(Fe). This MOF is prepared by mixing iron powder and an organic ligand such as benzenetricarboxylic acid and adding hydrofluoric acid. Nitric acid is then added, followed by water and heating for a specific time and temperature until the structure is formed. The process can also be done without hydrofluoric acid. In the case of ferric nitrate, benzenetricarboxylic acid and water are mixed under stirring at a specific pressure, temperature and time, after which a solvent extraction is carried out with ethanol and then dried. 2. Preparation of MOF-5: MOF-5 is prepared by using solvothermal synthesis. Zinc nitrate hexahydrate and 1,4-benzenedicarboxylic acid are dissolved in DMF. The solution is kept in a closed vessel and white crystals are observed after heating the reaction mixture. During filtration, the crystals are washed several times with fresh solvent. The solid thus formed is stored under dry DMF. 3. Preparation of chromium-based MOFs such as MIL-101(Cr): These are typically prepared by heating a mixture of terephthalic acid, chromium nitrate, hydrofluoric acid, and water, followed by filtering, washing, and drying. This procedure can also be performed without the use of hydrofluoric acid. 4. Preparation of Cu-BTC: The synthesis of Cu-BTC is carried out by mixing 1,3,5 benzenetricarboxylic acid in methanol and N,N-dimethylformamide. Another solution is prepared by mixing copper acetate monohydrate in an ethanol / distilled water mixture. Both solutions are stirred separately. The solution containing 1,3,5 benzenetricarboxylic acid is added to the other solution and sonicated. The suspension is then thermally treated in an autoclave. The resulting blue product is separated, washed, and dried. 5. Preparation of Aluminum Fumarate: This MOF is prepared by conventional techniques using aluminum metal salt and fumaric acid to provide a bidentate ligand to coordinate the aluminum ion and form a metal-organic framework. In known techniques, the precipitation reaction proceeds in a basic aqueous medium. The moisture adsorption properties of aluminum fumarate provide a major advancement for MOF-based sorption thermal methods due to its s-shaped isotherm and narrow hysteresis in typical moisture adsorption applications. 6. Preparation of MOF-801 P: This is prepared by dissolving fumaric acid and zirconium oxychloride in a heated DMF / formic acid solvent mixture. The resulting white precipitate is filtered, washed and dried. 7. Preparation of CAU-10H: It is prepared by mixing 1,3 benzenedicarboxylic acid, aluminum sulfate, dimethylformamide, and water, followed by heating for a specific time, cooling, and then filtering, washing, and then drying. 8. Preparation of CPO-Ni-27: This MOF is typically prepared by dissolving 2,5-dihydroxyterephthalic acid in tetrahydrofuran. A nickel(II) salt, such as nickel(II) acetate tetrahydrate, is dissolved in water, and the two solutions are then mixed, heated, filtered, washed, and dried. Alternatively, a mixture of 2,5-dihydroxyterephthalic acid, tetrahydrofuran, water, and nickel acetate as described above may be mixed together, and the solution is subjected to heating, filtering, washing, and drying.
[0022] Covalent organic frameworks are typically prepared by solvothermal, sonochemical, ionochemical, microwave-mediated, mechanochemical, and surface-directed synthesis techniques.
[0023] ZIFs are typically prepared in the art by solvothermal or hydrothermal synthesis, in which a hydrated metal salt, an imidazole bearing an acidic proton, a solvent, and a substrate are heated, if necessary, to effect the formation of a zeolite-imidazolate structure.
[0024] Usually, all the prior art methods other than the spraying method result in the formation of either a powder that is subsequently mixed with a binder before use, or a finished MOF, COF or ZIF powder that is deposited on the substrate to which the structure must be applied, when the substrate is coated with the binder, according to known techniques. US Patent No. 8,466,825 discloses a process for preparing multidimensional microporous metal-organic compounds by milling metals in ionic form with bridging organic ligands to obtain MOFs. This procedure can be carried out with or without a solvent according to this disclosure.
[0025] No. 9,815,222, which is in the same group as U.S. Pat. No. 8,466,825, discloses a further development, a continuous production method in which the metal in ionic form is simply mixed with a bridging organic ligand under conditions of shear and pressure to form a covalent bond, resulting in ostensibly higher yields.
[0026] US Patent No. 9,763,452 discloses a method for preparing MOFs that involves the use of low temperatures and solvents. The disclosed method essentially focuses on combining dihydroxyterephthalic acid in an aqueous basic solution of metal salts.
[0027] US Pat. No. 9,782,745 discloses a wet method for preparing MOFs for carbon dioxide adsorption in which metal ions and organic ligands are reacted in solvents such as water and alcohols at a desired temperature.
[0028] US Patent No. 8,697,191 discloses a process for essentially forming a coating or layer of a porous metal-organic framework (MOF) on the surface of a support, and is limited to spraying a solution containing a solution of metal ions and organic ligands to form layers on the surface, either sequentially or simultaneously. One inherent limitation of this process is that it can only be used for spraying only on the external surface of a substrate, when the substrate is formed into a specific shape, such as a tube, cylinder, or honeycomb structure. The process of this patent generally involves the use of a spray drum on which the substrate is placed for spraying to create a layer of MOF coating. The process of this patent, when carried out, results in a coating layer having a basis weight of less than 5 GSM, although the document itself claims a basis weight of up to 100 GSM. The surface includes natural and / or synthetic fibers, and the method is limited by its unsuitability for use where high temperatures of 100° C. or higher are possible, for example for activation. There is also no disclosure of the possibility of using this method with inert fibers as substrates, such as glass fibers, ceramic fibers, etc.
[0029] US Patent No. 8,697,191 discloses the use of only the following substrate materials: metallic and non-metallic materials. Metallic substrates limit the level of active material deposition. The non-metallic materials identified in the patent are limited to natural and organic fibers. This choice of substrate material has a direct impact on the temperature of both manufacture and use. There is no teaching that the process can be carried out independently of the nature of the substrate. For example, a serious limitation of the substrate properties is its reactivity / dependence on the temperature in manufacture and use. Non-metallic substrates such as those identified in this patent, i.e. natural fibers and organic materials, have serious temperature limitations at the point of use. Such materials essentially cannot be used in applications where the temperature can rise above the degradation point of the base substrate. US Patent No. 9,884,309 describes synthetic MOF crystallites of ZIF-8 structure, UiO-66, MIL-101, ZIF-90; including a binder and optionally one or more additives at 10% by weight or less. US Patent Application Publication No. 2013 / 0274087(A1) describes the development of covalently bonded MOFs on surface-treated substrates for adsorbing gases / toxic chemicals.
[0030] Prior art for the preparation of COFs and ZIFs: US Patent No. 7,582,798 discloses covalent organic frameworks comprising boron clusters linked together by multiple linking groups. US Patent No. 8,796,462 discloses zeolitic imidazolate frameworks. The preparation methods disclosed therein include organic solvents such as anhydrous tetrahydrofuran and hexane. US Patent No. 9,376,453 discloses the preparation of zeolitic imidazolate frameworks in aqueous systems at room temperature, where, inter alia, homogeneity is obtained by using auxiliary agents or additives as required.
[0031] WO 2016 / 055228 discloses a microwave-mediated method for producing MOFs or COFs. The method involves forming a reaction solution of precursors and exposing the reaction solution to microwave irradiation in a continuous flow state after mixing. The MOFs or COFs so formed are withdrawn and then washed and dried if necessary. The method involves the explicit use of a mixing means prior to microwave irradiation. The MW irradiation acts as a reaction igniter and therefore the method is very energy consuming.
[0032] The synthesis of MOFs by slow evaporation processes involves mixing solvents, increasing the solubility of reagents, and evaporating low boiling point solvents quickly, and is an alternative to energy-intensive room temperature synthesis (Ohi et al., 2004; Du et al., 2005; Halper et al., 2006; Yoo et al., 2011). Solvothermal synthesis usually involves high boiling point solvents, commonly using organic solvents such as dimethylformamide, diethylformamide, ethanol, methanol, acetone, and acetonitrile, and the desired nanoscale morphology requires high heat resistant vessels / autoclaves and long reaction durations (Wang & Ying, 1999). Nano-sized crystals can be rapidly grown by employing microwave-assisted solvothermal synthesis (Bux et al., 2009; Klinowski et al., 2011; Hidelang et al., 2012). In industry, the synthesis of MOFs is favored by electrochemical processes involving metal electrodes as a source of ionic metal and its dissolution in a mixture of organic linkers and electrolytes (Martinez Joaristi et al., 2012). Solvent-free synthesis leads to the formation of MOFs (Beldon et al., 2010) and ZIFs (Friscic et al., 2013) by mechanochemical processes where small amounts of liquid may be added in a liquid-assisted grinding (LAG) process. The extreme conditions generated by sonochemical synthesis lead to homogeneous nucleation centers and reduced crystallization times compared to solvothermal synthesis (Arul Dhas et al., Aslani & Morsali, 2009; Jung et al., 2010; Kim et al., 2011).
[0033] The above disclosure also describes various industrial applications of MOFs, COFs, and ZIFs, such as the separation of propane from propene, use in preparing catalytic filters, sensing applications, gas separation applications, etc. In all of the above applications, pre-prepared / synthesized MOFs / COFs / ZIFs are typically coated or deposited on a suitable substrate.
[0034] The prior art for dehumidification applications typically discloses the use of metal silicates, silica gels, and the like.
[0035] US Patent No. 4,911,775 describes a process for forming a honeycomb matrix which is impregnated with water glass before or after the lamination process. The matrix is then immersed in an aqueous solution of aluminum sulfate or magnesium sulfate to form a silicate hydrogel. Washing and drying of the matrix is carried out to obtain a dehumidifying element, where a metal silicate is deposited in the gaps between the fibers of the inorganic substrate.
[0036] US Patent No. 6,344,073 describes a process for obtaining dehumidifying materials comprising silica gel and metal oxides, prepared by adhering alkali silicates / alkoxysilanes to inorganic fibers and then immersing the impregnated substrate in a solution containing iron salts / iron / other metal salts, followed by drying.
[0037] US Patent No. 5,505,769 describes a humidity exchanger element formed from a honeycomb matrix including flat and corrugated sheets of inorganic fiber substrate, in which the adsorbent formed is an aerogel, which is a silicate of titanium or titanium-aluminum.
[0038] US Pat. No. 6,265,030 describes preparing a dehumidifying element by first impregnating a substrate with water glass and then immersing it in an aqueous solution of a metal salt and an acid.
[0039] US Pat. No. 5,254,195 describes a process for preparing moisture exchange elements by impregnating a substrate with an aqueous solution containing colloidal silica, an acid, and a metal salt, followed by drying and gelling.
[0040] No. 9,327,268 describes the formation of an in situ synthesized macroporous desiccant-based honeycomb matrix. The process involves impregnating a substrate with water glass, followed by treatment with aqueous metal salts or acid solutions, or a combination of both, followed by washing and drying.
[0041] There is growing interest in the use / applications of MOFs, COFs, or ZIFs in various industries / applications, such as VOC, CO2, and gas separation, carbon capture, hydrogen storage, catalysis, dehumidification, methane storage, energy storage, biodegradable filters, catalytic filters, gas storage, carbon capture, drug delivery, bioalcohol capture and dehydration, and / or gas / moisture adsorption applications.
[0042] Obviously, such applications of MOFs, COFs, and ZIFs, in practice, necessarily require the use of binders and separate steps of coating or deposition, regardless of the nature of the application - gas exchange, catalysis, etc. Such techniques are necessarily expensive and time consuming, and require greater efforts in ensuring uniformity of deposition, as well as maintaining the structural integrity of the structure to be bonded to the substrate, for example. Again, in such prior art applications where multiple laminates / sheets of substrates are used, it becomes necessary to use adhesive systems to ensure the bond between the sheets, especially when they are of different shapes, such as single facers.
[0043] Prior art applications of these materials also require separate, time-consuming and expensive analyses to determine the compatibility of a particular binding and / or adhesive system with a particular MOF, COF or ZIF, as well as to determine the percentage loading and the difficulty of ensuring higher basis weights of the deposition or coating. The choice of substrate is also limited to materials that are not inert at the high temperatures typically required for activation of the deposited or coated materials. Also, the amount of loading on the substrate, as well as the uniformity of the thickness of the deposition / coating of the adsorbent material, are generally not easily controllable. These disadvantages necessarily limit the scope of industrial applicability of such materials in areas where there is a high level of temperature sensitivity, and also limit the uniform reproducibility of the method. This means that separate deposition / coating protocols must be devised for every industrial application.
[0044] As will be seen, it is desirable to provide a method for synthesizing MOFs, COFs, and / or ZIFs that is easily reproducible for a wide range of industrial applications, regardless of the nature of the substrate or application, and that completely or substantially avoids the use of binders at any stage. In addition, such a method should also be formulated such that higher performance efficiency is ensured by ensuring a higher basis weight in forming the adsorbent product, where the level of temperature sensitivity of activation or regeneration is minimized.
[0045] The applicants herein are pioneers in addressing such problems inherent in HVAC industry applications of silica gel, metal silicates, and zeolites, alone or in combination, without the use of binders. Indeed, the applicants herein have developed a novel and innovative in-situ method for forming special metal silicates on porous substrates that has provided flexibility, ease of use, and performance efficiency far beyond expectations. Such efforts by the applicants herein and others have been limited to inorganic materials / adsorbents to date.
[0046] It is an object of the present invention to provide a novel method for the in situ synthesis of MOFs, COFs and ZIFs in and on porous substrates at six times the mass of the bare substrate, as well as to overcome the problems associated with the prior art.
[0047] It is another object of the present invention to provide for the fabrication of shaped substrates / matrices in any desired geometry, where MOFs, COFs, ZIFs can be synthesized or impregnated in situ for use in adsorption applications such as dehumidification or adsorption of CO2, VOCs, or other gases, etc., thereby producing substrates / matrices with a thickness of up to 1000m. 2 The very high surface area, often exceeding 1000 nm / g, and the low temperatures required for regeneration, typically less than 100° C., coupled with up to twice as high adsorbent loading, result in high energy efficiency, high performance, or both.
[0048] Despite their best efforts, the inventors have been unable to locate any prior art that teaches or guides towards the in situ synthesis of organic substructures, including materials such as MOFs, COFs, or ZIFs, in and on porous substrates and that have one or more of the following attributes: high surface area, porosity, selective adsorption, reactivity. [Prior art documents] [Patent documents]
[0049] [Patent Document 1] U.S. Patent No. 8,466,825 [Patent Document 2] U.S. Patent No. 9,815,222 [Patent Document 3] U.S. Patent No. 9,763,452 [Patent Document 4] U.S. Patent No. 9,782,745 [Patent Document 5] U.S. Patent No. 8,697,191 [Patent Document 6] U.S. Pat. No. 9,884,309 [Patent Document 7] US Patent Application Publication No. 2013 / 0274087 [Patent Document 8] U.S. Patent No. 7,582,798 [Patent Document 9] U.S. Pat. No. 8,796,462 [Patent Document 10] U.S. Patent No. 9,376,453 [Patent Document 11] International Publication No. 2016 / 055228 [Patent Document 12] U.S. Pat. No. 4,911,775 [Patent Document 13] U.S. Patent No. 6,344,073 [Patent Document 14] U.S. Pat. No. 5,505,769 [Patent Document 15] U.S. Patent No. 6,265,030 [Patent Document 16] U.S. Patent No. 5,254,195 [Patent Document 17] U.S. Patent No. 9,327,268 Summary of the Invention [Means for solving the problem]
[0050] The present invention provides a method for in situ synthesis of MOFs, COFs, or ZIFs on and within a porous substrate by contacting the porous substrate with a first solution and a second solution, which can form the MOFs, COFs, or ZIFs. The method of the present invention provides a flexible and easy-to-use method for producing MOFs, COFs, and / or ZIFs directly and in situ on and within a substrate, thereby achieving a higher and / or more controlled degree of formation, essentially overcoming or mitigating the problems associated with the prior art.
[0051] The method of the present invention is independent of MOFs, COFs, or ZIFs and is reproducible across a variety of applications.
[0052] In another embodiment, the present invention also provides a sorbent matrix in which one or more sorbents selected from the group consisting of MOFs, COFs, and ZIFs, or a combination of one or more of MOFs, COFs, and ZIFs, and an inorganic sorbent are synthesized in situ or impregnated thereon, as well as a method for in situ synthesis or impregnation applicable to produce such a sorbent matrix.
[0053] In yet another embodiment, the present invention also provides a desiccant wheel comprising an adsorbent matrix manufactured according to the previous embodiment, and the use of such a desiccant wheel.
[0054] In yet another embodiment, the present invention also provides a method for filtering adsorbates from a fluid using an adsorbent laden matrix comprising an adsorbent selected from one or more combinations of MOFs, COFs, ZIFs, MOFs, COFs, ZIFs, and inorganic adsorbents. [Brief description of the drawings]
[0055] [Figure 1a] Water uptake capacity at different RH for various conventional inorganic adsorbents (Source: Sorbent Systems / PNNL). Demonstrating that MOF adsorption capacity is higher than conventional adsorbents / desiccant materials. [Figure 1b] Water uptake capacity at different RH for various MOFs compared to silica gel (Source: PNNL), demonstrating that MOF adsorption capacity is higher than conventional adsorbents / desiccant materials. [Figure 1c] Adsorption and desorption curves of a particular S-type MOF (MOF-101) at different RH (Source: Janiak et al., Eur. J. Inorganic Chem., 2011 / PNNL) demonstrate that MOF adsorption capacity is higher than conventional adsorbents / desiccant materials. [Figure 2a]Water uptake capacity of various adsorbents at different time intervals at 25°C and 75% RH (Source: Sorbent Systems / PNNL), showing higher adsorption rates (kinetics) of MOFs compared to conventional adsorbents / desiccant materials. [Figure 2b] Water uptake capacity of MOF (Cu-BTC) at different exposure times, room temperature and 40% RH (Source: PNNL). Higher adsorption rates (reaction rates) of MOFs compared to conventional adsorbents / desiccant. [Figure 2c] Water uptake capacity of two different adsorbents at different exposure times, room temperature and 40% RH (Source: PNNL), showing the higher adsorption rate (kinetics) of MOFs compared to conventional adsorbents / desiccant. [Figure 3a] Water uptake capacity of various conventional adsorbents at different activation conditions (Source: Sorbent Systems / PNNL). It shows that MOFs have significantly lower desorption temperatures compared to conventional adsorbents / desiccant materials, which is advantageous in terms of the energy required for regeneration. [Figure 3b] Thermogravimetric analysis (TGA) curve of MOF (Cu-BTC) (Source: PNNL) shows that MOFs have a significantly lower desorption temperature compared to conventional adsorbents / desiccant materials, which is advantageous in terms of the energy required for regeneration. [Figure 3c] Thermogravimetric analysis (TGA) curve of MOF(CoCo) (Source: PNNL) shows that MOFs have a significantly lower desorption temperature compared to traditional adsorbents / desiccant materials, which is advantageous in terms of the energy required for regeneration. [Figure 4a] 1 shows XRD images of aluminum fumarate prepared according to one embodiment of the present invention, confirming the in situ synthesized materials as unique MOFs, COFs, and ZIFs, respectively, and validating the workability of the method of the present invention. [Figure 4b] FTIR images of COF-1 prepared according to the method of the present invention confirm that the in situ synthesized materials are unique MOFs, COFs, and ZIFs, respectively, and confirm the workability of the method of the present invention. [Figure 4c] 1 shows XRD images of ZIF-1 prepared according to the method of the present invention, confirming that the in situ synthesized materials are distinct MOFs, COFs, and ZIFs, respectively, and confirming the workability of the method of the present invention. [Figure 5a] FIG. 1 is a schematic diagram of a cross-sectional view of a porous flat substrate with MOFs synthesized in situ (on and within the substrate) according to the method of the present invention. [Figure 5b] FIG. 1 is a schematic diagram of a perspective view of a porous flat substrate in sheet form with MOFs synthesized in situ (on and within the substrate) according to the method of the present invention. [Figure 6] 1 is an exemplary depiction of various matrix shapes in which MOFs can be synthesized in situ (on and within porous substrates), achievable according to the methods of the present invention. [Figure 7] FIG. 1 is an exemplary depiction of a honeycomb matrix typically used in fluid exchange / filtration devices, where MOFs are synthesized in situ (on and within the porous substrate), which can be accomplished according to the methods of the present invention. [Figure 8] FIG. 1 is a schematic diagram of an in situ synthesis process according to the present invention showing the production of a honeycomb matrix using in situ synthesized aluminum fumarate by sequential impregnation. [Figure 9] FIG. 1 is a schematic diagram of the production of a honeycomb rotor via a simultaneous and in situ continuous synthesis process of an adsorbent of a substrate passing a continuously formed mixture of components A and B, which is then formed into a honeycomb substrate. [Figure 10] FIG. 1 is a schematic diagram of the fabrication of a preformed honeycomb matrix in which MOFs are synthesized in situ (on and within the porous substrate of the honeycomb) according to one embodiment of the present invention. [Figure 11] FIG. 13 is a schematic diagram of manufacturing a honeycomb matrix rotor by impregnating a substrate in a slurry of aluminum fumarate and forming it into a honeycomb rotor according to another embodiment of the present invention. [Figure 12]FIG. 2 is a schematic diagram of a pre-prepared honeycomb matrix rotor that is impregnated by immersion in a slurry of aluminum fumarate in accordance with one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0056] The following describes the method of the present invention and the implementation required to achieve the above-mentioned embodiments. The description is exemplary and should not be interpreted as limiting the scope of the present invention. Variations and modifications are possible without departing from the spirit and scope of the present invention.
[0057] Thus, the present invention provides in a first embodiment a novel and inventive method for the in situ synthesis of MOFs, COFs and / or ZIFs directly in and on substrates, regardless of industrial application or choice of substrate, providing high flexibility in the use and implementation of these materials by eliminating or minimizing the dependency on binding systems, choice of substrate, etc., as will be understood later.
[0058] One advantage of this in situ preparation method is that it allows MOF / COF / ZIF to be provided in or on a substrate in an amount of 0.5 to 6 times the basis weight of the substrate. In addition, the need for a binding system as required in the prior art is completely eliminated. The method of the present invention allows the preparation of substrates with MOFs, COFs, and ZIFs synthesized in situ without additional steps such as coating, curing, etc., which are required when powder-prepared MOF / COF / ZIF powders are used according to the prior art.
[0059] The present invention provides a method for the in situ synthesis of metal-organic frameworks, covalent organic frameworks, or zeolitic imidazolate frameworks into and onto porous substrates, where all materials synthesized are fully active materials except for the substrate.
[0060] The present invention also provides specific industrial applications that can employ in situ deposition of MOFs, COFs, and / or ZIFs, including, for example, humidity control applications, gas separation applications, gas storage, biodegradable filters, catalytic filters, carbon capture applications, sensing applications, energy storage / lithium battery applications, carbon capture, bioalcohol recovery, drug delivery, and the like.
[0061] The method of the present invention involves the preparation of a zeolitic imidazolate framework composed of different metal-organic frameworks and at least one bidentate organic compound coordinated to at least one metal ion, providing a framework in which in the case of covalent organic frameworks, at least one organic compound is covalently bonded to a second organic compound. The substrate may or may not contain water glass, silica sol, or any inorganic or organic material used as a hardener, for example in the corrugation of the substrate. This is a function of the specific industrial application and is not essential to the working of the in situ synthesis of the present invention.
[0062] Porous substrates of any desired shape or form can be made by selecting from one or more of the following: glass fiber, ceramic fiber, natural fiber, synthetic fiber, biosoluble fiber, pulp, etc., allowing the use of the substrate with or without additional processing, as well as synthetic materials up to 500°C or higher depending on the thermal stability of the particular MOF / COF / ZIF.
[0063] If desired, the substrate can be pre-treated with a hardener such as silica sol, alumina sol, polyvinyl alcohol, polyvinyl acetate, acrylate, or any other similar non-reactive material such as water glass.
[0064] In the method of the present invention, the substrate on which the MOF, COF or ZIF is synthesized in situ may be the substrate itself or a shaped matrix. The method essentially involves treating the substrate or matrix with a solution containing a monovalent, divalent, trivalent metal salt solution to aid in the formation of crystals in the case of MOFs, and with a solution of a bidentate or tridentate organic compound in the solution under the desired conditions of time and temperature. In the case of ZIFs, the same method can be repeated by replacing the bidentate or tridentate solution with a solution of a heterocyclic aromatic organic compound. The MOF or ZIF is formed in situ in and on the substrate at the time of treatment with the second solution. The components of the MOF / ZIF are not deposited, but are formed in situ during the reaction of the two solutions directly on and in the substrate without the need for a separate binder.
[0065] The metal solution may be a solution of a single metal. If the desired MOF must contain two or more metal ions, the solution may be a co-solution of two or more different solutions of the respective metal ions. Similarly, a mixture of solutions may be used to form different MOFs. Obviously, in the case of ZIFs with more than one metal component, or separate ZIFs, where a zeolite structure is required, the metal solution may be a mixture of solutions of different metals.
[0066] Similarly, the solution of the organic component may be a mixture of solutions of two or more organic linkers / ligands or solutions of two or more heteroaromatic organic compounds.
[0067] An important aspect of the present invention is the flexibility of the approach during in situ synthesis. The substrate can be contacted with the first and second solutions sequentially in any order, simultaneously, or even as a co-solution containing a mixture of both the first and second solutions. The reaction rate (MOF, COF, or ZIF formation) can be controlled by using the appropriate reaction accelerator or retarder.
[0068] The time and temperature conditions during the reaction (in situ formation) step can be controlled to tailor the loading of MOFs / ZIFs / COFs onto the substrate or matrix, again providing flexibility to customize the substrate / matrix for a specific application.
[0069] In another embodiment of the invention, the first or second solution can provide other components (such as water glass, inorganic acid, etc.) to allow co-synthesis of MOFs, COFs, or ZIFs with an inorganic adsorbent. The inorganic adsorbent so formed can be silica gel and / or metal silicates, or a specific inorganic adsorbent.
[0070] In a further embodiment of the invention, an inorganic material (such as a zeolite) can be mixed with the first or second solution such that the in situ synthesized MOFs, COFs, or ZIFs encapsulate the inorganic material.
[0071] In another embodiment of the invention, the substrate after treatment with the first solution is converted to the desired matrix morphology and then treated with the second solution.
[0072] In yet another embodiment, the substrate is treated with both the first and second solutions, either sequentially or simultaneously, and then transformed into the desired matrix geometry.
[0073] After treatment with the reactant solutions (first and second solutions), the substrate / matrix is washed and dried. Drying can be by any conventional means, such as a drying chamber, or by natural drying. The treated substrate can be heated for activation purposes.
[0074] The metal can be selected from the group consisting of iron, nickel, titanium, zirconium, chromium, aluminum, zinc, tin, lead, magnesium, copper, cobalt, and other monovalent, divalent, or trivalent metals. The metal component can be used as the metal itself or in the form of a salt. Examples of metal salts that can be used include ferric nitrate, ferric chloride, ferrous chloride, chromium nitrate, chromium chloride, aluminum sulfate, aluminum chloride, aluminum bromide, aluminum hydrogen sulfate, aluminum dihydrogen phosphate, aluminum monohydrogen phosphate, aluminum phosphate, aluminum nitrate, nickel acetate, zirconium oxychloride, zinc nitrate, zinc acetate, copper acetate, copper nitrate, cobalt nitrate, magnesium nitrate, and the like. The aluminum salt is preferably a material capable of providing aluminum (III) ions. The metal salt can be present in the form of an alkoxide, acetonate, halide, sulfite, as a salt of an organic or inorganic acid containing oxygen, or a mixture thereof. The alkoxide is, for example, methoxide, ethoxide, n-propoxide, i-propoxide, n-butoxide, i-butoxide, t-butoxide, or phenoxide. The acetonate is, for example, acetylacetonate. The halide is, for example, chloride, bromide, or iodide. The organic acid containing oxygen is, for example, formic acid, acetic acid, propionic acid, or another alkyl monocarboxylic acid. The inorganic acid containing oxygen is, for example, sulfuric acid, sulfurous acid, phosphoric acid, or nitric acid.
[0075] The metal components when used in the present invention are usually in the form of an aqueous mixture. Alternatively, the metal salts may also be in suspension or aqueous solution, or a combination of water and an organic or inorganic solvent. The choice of solvent depends on the metal salt in question.
[0076] Examples of solvents used are water, methanol, ethanol, n-propanol, iso-propanol, n-butanol, isobutanol, t-butanol, pentanol, hexanol, dimethylsulfoxide, N,N-dimethylformamide, N,N-diethylformamide, toluene, acetonitrile, dioxane, N,N-dimethylacetamide, benzene, chlorobenzene, tetrahydrofuran, ethyl acetate, methyl ethyl ketone, pyridine, sulfolane, glycol, N-methylpyrrolidone, diethylamine, triethylamine, gamma-butyrolactone, cyclohexanol, acetylacetonate, mesitylene, and other similar aqueous, non-aqueous, aliphatic, aromatic, organic, inorganic solvents, and mixtures thereof.
[0077] The bidentate or tridentate organic compounds are oxalic acid, tartaric acid, succinic acid, 1,4-butanedicarboxylic acid, 1,4-butene-dicarboxylic acid, 4-oxopyran-2,6-dicarboxylic acid, decanedicarboxylic acid, 1,8-heptadecanedicarboxylic acid, 1,6-hexanedicarboxylic acid, heptadecanedicarboxylic acid, acetylenedicarboxylic acid, 1,9-heptadecanedicarboxylic acid, 1,2-benzenedicarboxylic acid, 1,3-benzenedicarboxylic acid, 2,3-pyridinecarboxylic acid, pyridine-2,3-dicarboxylic acid, 1,4-benzenedicarboxylic acid, p-benzenedicarboxylic acid, imidazole-2,4-dicarboxylic acid, 2-methylquinoline-3,4-dicarboxylic acid, quinoline-2 ,4-dicarboxylic acid, quinoxaline-2,3-dicarboxylic acid, 6-chloroquinoxaline-2,3-dicarboxylic acid, 1,3-butadiene-1,4-dicarboxylic acid, 4,4'-diaminophenylmethane-3,3'-dicarboxylic acid, quinoline-3,4-dicarboxylic acid, diimidedicarboxylic acid, pyridine-2,6-dicarboxylic acid, 2-methylimidazole-4,5-dicarboxylic acid, 7-chloro-4-hydroxyquinoline-2,8-dicarboxylic acid, thiophene-3,4-dicarboxylic acid, tetrahydropyran-4,4-dicarboxylic acid, perylene-3,9-dicarboxylic acid, 2-isopropylimidazole-4,5-dicarboxylic acid, perylene dicarboxylic acid, Pluriol E 200-dicarboxylic acid, 3,5-cyclohexadiene-1,2-dicarboxylic acid, octanedicarboxylic acid, pentane-3,3-carboxylic acid, 3,6-dioxaoctanedicarboxylic acid, 4,4'-diamino-1,1'-biphenyl-3,3'-dicarboxylic acid, 4,4'-diaminobiphenyl-3,3'-dicarboxylic acid, benzidine-3,3'-dicarboxylic acid, 1,1'-binaphthyl dicarboxylic acid, 1,4-bis(phenylamino)benzene-2,5-dicarboxylic acid carboxylic acid, 7-chloro-8-methylquinoline-2,3-dicarboxylic acid, 1-anilinoanthraquinone-2,4'-dicarboxylic acid, 1,4-bis(carboxymethyl)piperazine-2,3-dicarboxylic acid, phenylindanedicarboxylic acid, 7-chloroquinoline-3,8-dicarboxylic acid, polytetrahydrofuran 250-dicarboxylic acid, 1-(4-carboxy)phenyl-3-(4-chloro)phenylpyrazoline-4,5-dicarboxylic acid, 1,4,5,6,7,7-Hexachloro-5-norbornene-2,3-dicarboxylic acid, 1,3-dibenzyl-2-oxoimidazolidine-4,5-dicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, naphthalene-1,8-dicarboxylic acid, 1,3-dibenzyl-2-oxoimidazolidine-4,5-cis-dicarboxylic acid, 2,2'-biquinoline-4,4'-dicarboxylic acid, 2-benzoylbenzene-1,3-dicarboxylic acid, pyridine-3,4 dicarboxylic acid, 3,6,9-trioxaundecane dicarboxylic acid, Pluriol E 300 dicarboxylic acid, Pluriol E 400 dicarboxylic acid, hydroxybenzophenone dicarboxylic acid, Pluriol E 600-dicarboxylic acid, pyrazole-3,4-dicarboxylic acid, bis(4-aminophenyl)sulfondiimide-dicarboxylic acid, 5,6-dimethyl-2,3-pyrazinedicarboxylic acid, bis(4-aminophenyl)etherdiimide-dicarboxylic acid, 2,3-pyrazinedicarboxylic acid, 4,4'-diaminodiphenylmethanediimide-dicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,3-adamantanedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 8-methoxy-2,3-naphthalenedicarboxylic acid, 8-sulfo-2,3-naphthalenedicarboxylic acid , anthracene-2,3-dicarboxylic acid, 8-nitro-2,3-naphthalenecarboxylic acid, 2',3'-diphenyl-p-terphenyl-4,4''-dicarboxylic acid, (diphenyl ether)-4,4'-dicarboxylic acid, 4(1H)-oxothiochromene-2,8-dicarboxylic acid, imidazole-4,5-dicarboxylic acid, 5-tert-butyl-1,3-benzenedicarboxylic acid, 7,8-quinolinedicarboxylic acid, 4,5-imidazoledicarboxylic acid, etc., or 1,3,5-benzenetricarboxylic acid, 1,3,5-tris(4-carboxyphenyl)benzene, etc., can be derived from dicarboxylic acids.
[0078] Viscosity enhancers / additives are added to increase the filling of the substrate. Examples of additives include xanthan gum, sodium alginate, hydroxypropyl methylcellulose, guar gum, starch, ethylene glycol, etc.
[0079] In the case of ZIF, the organic ligand is usually selected from the group of heteroaromatic organic compounds consisting of imidazole, benzimidazole, chlorobenzimidazole, nitroimidazole, 2-methylimidazole, imidazole-2-carboxaldehyde, etc. It may be dissolved in an organic solvent or water. The metal component is usually a metal such as zinc, cobalt, or iron in salt form. The actual form used may be in powder form or dissolved in any organic, aqueous, or inorganic solvent.
[0080] In the case of the covalent organic framework, the materials include, for example, 1,3,5-triformylphloroglucinol, 1,4-benzenediboronic acid, tert-butylsilanetriol, and p-phenylenediamine. The components can be dissolved in a solvent such as 1,2-dichloroethane, 1,4-dioxane, toluene, or mesitylene-dioxane mixtures.
[0081] The advantage of the method of the present invention is that in most cases, the order of impregnation to reaction is not specific to the reactants. Thus, for example, any group of materials may be impregnated into a porous substrate, and then the substrate is treated with the other group to form MOFs / COFs or ZIFs in situ. This also allows control of the loading, loading depth, and loading uniformity, effectively eliminating the need to use a bonding system to attach the MOFs to the substrate.
[0082] While the following discussion refers to certain specific MOFs, it should not be construed in a limiting manner, as the in situ formation method can also be used to form non-exemplary MOFs, COFs, or ZIFs by appropriately modifying the process.
[0083] In the case of MIL-100(Fe), the preparation method includes mixing 1,3,5-benzenetricarboxylic acid in an organic solvent such as ethanol or dimethylformamide. A second solution of an iron salt such as ferric nitrate is again prepared, either as an aqueous solution or as a solution in an organic solvent such as methanol. The porous substrate may be treated with either solution before being treated with the second solution. The order of treatment is not important. The second treatment is carried out at a specific time and temperature to form the MOFs in situ, up to a loading of up to 6 times GSM or more relative to the basis weight of the porous substrate.
[0084] In the case of aluminum fumarate, a porous metal-organic framework is formed by the coordination of fumarate ions to aluminum(III) ions. The framework is formed in situ on and within the substrate. The source of bidentate fumarate ions is fumaric acid and the source of aluminum(III) ions is aluminum sulfate. The metal-organic frameworks produced are the result of the reaction of an aluminum compound and a bidentate organic compound in aqueous media in the presence of a base at different reaction temperatures and reaction times.
[0085] The porous structure comprises at least one bidentate ligand based on fumaric acid and a trivalent metal salt based on aluminum ions. The powdered aluminum fumarate formed is attached onto the surface of the substrate by using a suitable inorganic or organic binder. Water is used as a solvent in the reaction. A simple alkali metal hydroxide, preferably sodium hydroxide or potassium hydroxide, is used.
[0086] In another embodiment of the present invention, MOFs, COFs, and ZIFs prepared in situ or by conventional techniques are also useful for heat exchange or adsorption applications. For shaped matrices, such as honeycomb matrices, the use of MOFs, COFs, or ZIFs prepared in situ or by conventional dry / wet methods or coating / deposition methods has shown great advantages over the use of conventional zeolite or silica gel technology, including lower regeneration temperatures, therefore lower energy use, faster moisture absorption, and much higher adsorption uptake.
[0087] The present invention also provides methods for forming, by in situ synthesis or deposition, metal-organic frameworks in or on heat exchanger elements suitable for low, medium or high humidity applications, and on such humidity exchanger elements.
[0088] The applicants herein have earlier demonstrated the advantages of in-situ synthesis of metal silicate microporous desiccants in honeycomb structures used in humidity control applications compared to systems that are produced and then coated. The use of in-situ synthesized MOFs, or COFs, or ZIFs in honeycomb structures can be expected to offer significant advantages over coated MOFs / COFs or ZIFs, especially since the depth of formation is greater than in the prior art. Preliminary studies have shown active materials synthesized / deposited at up to 6 times GSM levels compared to the figures of up to 100 GSM claimed (although not confirmed or demonstrated) in the prior art, such as those disclosed in US Patent No. 8,697,191.
[0089] The present invention also relates to humidity exchanger elements suitable for low, medium and high humidity applications, produced by laminating corrugated paper and liner paper with many small channels with active metal-organic frameworks (MOFs) synthesized or deposited in situ using porous or non-porous substrates. Powdered or granular materials are also suitable for use in humidity exchange. A notable advantage of the method of the present invention is that it allows the user to select the level of loading of MOFs, COFs or ZIFs synthesized in situ according to his or her specific needs. Thus, even loadings of 0.2% to 600% (based on the bare mass of the substrate) of the adsorbent can be selected and implemented according to the specific industrial application.
[0090] The above disclosure is non-limiting, and variations and modifications are possible in any manner without departing from the spirit and scope of the present invention. The following examples describe various embodiments of the present invention and involve the in situ synthesis of MOFs, COFs, and ZIFs using the methods of the present invention. EXAMPLES
[0091] In all the following examples, a glass fiber substrate is utilized, which has a porosity capable of holding up to 6-8 times its own mass of water glass. A drying step, when performed, was used by air drying. Activation is performed at 140°C for 2 hours.
[0092] Example 1: In situ synthesis of aluminum fumarate A: Using untreated substrate: (Example 1a: Using potassium hydroxide without additives) Solution A is prepared in three parts by dissolving potassium hydroxide in water followed by addition of fumaric acid under stirring, the ratio of elements being different as listed in Table 1a below. Solution B is prepared by dissolving 100g of aluminum sulfate in 500ml of water. The substrate has a basis weight of 33GSM. Solution B and the substrate are also divided into three separate parts - each used with one of the respective parts of solution A. The substrate is immersed in the respective parts of solution A at room temperature and then naturally dried. The dried substrate is then treated with solution B at a temperature of 80°C and a time of 15 minutes to initiate the reaction. After the reaction is completed, the substrate is washed with water to remove any by-products and then exposed to natural drying before being activated in a drying chamber. The loading percentage of the MOF (aluminum fumarate) synthesized in situ on the substrate was investigated. The amount of raw materials in solution A and the results of the tests are listed in Table 1a below.
[0093] [Table 1]
[0094] (Example 1b: Using potassium hydroxide with additive and increasing the number of dips) Solution A is prepared in three parts by dissolving 120 g of potassium hydroxide in 450 ml of water, followed by the addition of 99 g of fumaric acid under stirring, followed by the addition of 2 g of xanthan gum as an additive. Solution B is prepared by dissolving 100 g of aluminum sulfate in 200 ml of water. The substrate is a substrate of 33 GSM basis weight. Substrate parts are immersed in parts of solution A with different numbers of immersions (2, 3, and 4 times respectively), subjected to intermediate drying to enhance the loading of component / reactant A, followed by final drying, and then immersed in respective parts of solution B to initiate the in situ formation of aluminum fumarate on the substrate. The reaction temperature is 75° C. and the reaction time is 30 minutes. The substrate is then air-dried and activated in a drying chamber, after being washed respectively to remove by-products. The loading percentage of the in situ synthesized MOFs and the effect of successive immersions on the loading percentage were investigated. Moisture sorption at 50% RH was investigated using Belsorp Aqua 3. The results are shown below in Table 1b. The adsorption of about 35% correlates very well with the highest adsorption reported in the literature of 33-38% for aluminum fumarate at 50% RH.
[0095] [Table 2]
[0096] Example 1c: Use of potassium hydroxide with silica sol and additives The procedure of Example 1a was followed, except that 7 parts of solution A were prepared with different amounts of potassium hydroxide and xanthan gum additives. Silica sol is also added to solution A under continuous mixing. Solution B is the same as in Example 1b above. The substrate was constructed with a basis weight of 33 GSM. Substrate parts were immersed in different parts of solution B at different temperatures and times. This was followed by washing, air drying, and activation in a drying chamber. The effect of different amounts of reactants in solution A, reaction times, and reaction temperatures on the fill percentage was investigated. Details are given in Table 1c below.
[0097] [Table 3]
[0098] Example 1d: Using Potassium Hydroxide with Polyvinyl Alcohol and Additives Six parts of solution A are prepared using the procedure of Example 1c, except that polyvinyl alcohol is added under mixing instead of silica sol. The amounts of potassium hydroxide, xanthan gum additive, and polyvinyl alcohol are varied. Solution B is prepared as in Example 1b. The substrate is composed of a basis weight of 33 GSM. The substrate is treated with solution A and solution B following the procedure of Example 1c, except that the reaction temperature and time are varied. The loading percentage of MOFs synthesized in situ on the substrate and the effect of varying the amount of reactants, reaction temperature, and reaction time on the loading percentage and the adsorption percentage at 50 RH% are investigated. The adsorption percentage study is carried out on a Belsorp Aqua 3. The process details are as follows in Table 1d (Table 4). Sample 3 in Table 1d below was cross-validated by XRD with characteristic peaks at 2θ positions 10.410, 14.750, 18.270, 20.810, and 26.570, which confirmed the formation of aluminum fumarate in situ. The XRD is shown in Figure 4a.
[0099] [Table 4]
[0100] B: Use a pretreated substrate (Example 1e. Using sodium hydroxide without additives) Solution-A is prepared in 5 parts at ambient temperature by dissolving sodium hydroxide in water. Then, fumaric acid is added thereto with continuous stirring to obtain a solution of sodium fumarate. The substrate is pre-treated with 5% silica sol, naturally dried and divided into 5 equal parts. Each pre-treated substrate part is immersed in a respective part of solution-A at room temperature and then naturally dried. Solution-B is prepared in 5 parts by dissolving aluminum sulfate in water at ambient temperature. Then, each of the 5 pre-treated substrate parts already immersed or immersed in solution-A is immersed / immersed in a separate part of solution-B at a given temperature but for different times to obtain different amounts of aluminum fumarate in situ synthesized on and within the substrate, followed by natural drying. The substrate is then washed with water to remove any by-products formed during the reaction and exposed to natural drying before being activated in a drying chamber. Each portion of solution A contained 25.2 g NaOH dissolved in 200 ml water and the amount of fumaric acid added was 24.3 g. The basis weight of the substrate was 33 GSM. Solution B contained 100 g aluminum sulfate dissolved in 500 ml water. The reaction temperature was 80° C. The effect of reaction time on the loading percentage (in situ synthesized MOF on the substrate) was investigated. The obtained results are shown in Table 1e below.
[0101] [Table 5]
[0102] (Example 1f. Using sodium hydroxide with additives) The procedure described in Example 1e was followed, except that during the preparation of solution A, 0.5 g of xanthan gum was also added under stirring after the addition of fumaric acid, followed by further stirring. The basis weight of the substrate was 33 GSM. The effect of the additives on the reaction time, reaction temperature, and loading percentage (of the in situ synthesized MOF on the substrate) was investigated. The results obtained are listed in Table 1f below.
[0103] [Table 6]
[0104] (Example 1g. Using potassium hydroxide with additive) The procedure described in Example 1f is followed, except that in the preparation of solution A, 120 g of potassium hydroxide is used in 450 ml of water containing 99 g of fumaric acid instead of sodium hydroxide. The amount of xanthan gum additive is 2 g. The basis weight of the substrate is 33 GSM. The effect of varying reaction temperature on the loading percentage of in situ synthesized MOFs on the substrate is investigated. The results are shown in Table 1g below.
[0105] [Table 7]
[0106] (Example 1h: Additives are used, sodium hydroxide, polyvinyl alcohol are used) The procedure described in Example 1e is followed, except that after the addition of fumaric acid, 0.5 g of xanthan gum additive is also added, followed by further stirring. Then, 10 ml of a 10% solution of polyvinyl alcohol is also added to the resulting solution and mixed well. Solution B contains 100 g of aluminum sulfate in 200 ml of water. The basis weight of the substrate is 33 GSM. The effect of different reaction temperatures and reaction times on the loading percentage of MOFs synthesized in situ on the substrate was investigated, and the results are shown in Table 1h.
[0107] [Table 8]
[0108] In all of the above examples, the loading of in situ synthesized aluminum fumarate on and within the substrate is measured by taking the difference in actual mass between the bare substrate and the loaded substrate and dividing the result by the bare mass of the substrate, which was found to be in the range of 0.1 to 6 times the mass of the bare substrate.
[0109] Example 2: In situ synthesis of MIL-100(Fe) A: Use an untreated substrate (Example 2a: Using sodium hydroxide + additive + ferric chloride) Six parts of solution A are prepared by dissolving different amounts of 1,3,5-benzenetricarboxylic acid in a solution of 10 g of sodium hydroxide in 250 ml of water, followed by adding different amounts of xanthan gum as an additive under stirring. Solution B is prepared by dissolving 30 g of ferric chloride in 500 ml of water. Six parts of substrates with a basis weight of 33 GSM are prepared. Each part is immersed in a respective portion of solution A, then air-dried, and then immersed in solution B to initiate the reaction. The reaction temperature and time are varied. This is followed by cleaning of the drying chamber, air-drying, and activation. The loading percentage of MOFs synthesized on the substrate and the effect of temperature and time variations on the loading percentage are investigated. The results are shown in Table 2a below.
[0110] [Table 9]
[0111] (Example 2b: Using sodium hydroxide + additive + ferric nitrate) The procedure of Example 2a was followed, except that solution A was prepared by dissolving 13 g of 1,3,5-benzenetricarboxylic acid in an aqueous basic medium of 10 g of sodium hydroxide in 250 ml of water, followed by the addition of 1 g of xanthan gum under continuous stirring, and solution B was prepared by dissolving 30 g of ferric nitrate in 500 ml of water. The substrate has a basis weight of 33 GSM. The soaking and reaction procedures are as described in Example 2a. The reaction temperature is maintained at 95° C., while the reaction time is varied. The effect of varying the reaction time on the loading percentage of the MOFs synthesized in situ on the substrate is investigated. The results are shown in Table 2b below.
[0112] [Table 10]
[0113] (Example 2c: Using sodium hydroxide + additive + polyvinyl alcohol + ferric chloride) The procedure of Example 2a is followed, except that solution-A is prepared by dissolving 10.4g of 1,3,5-benzenetricarboxylic acid in an aqueous basic medium of 10g of sodium hydroxide in 250ml of water, followed by the addition of 0.75g of xanthan gum under continuous stirring, followed by the addition of 10ml of polyvinyl alcohol. Solution-B is prepared by dissolving 30g of ferric chloride in 500ml of water. The procedure of immersing the substrate (having 33GSM) in solutions A and B is the same as in Example 2a. The reaction temperature and reaction time are varied. The effect of varying reaction time and temperature on the loading of in-situ synthesized MOFs on the substrate is investigated. The details of the process are as follows in Table 2c (Table 11).
[0114] [Table 11]
[0115] (Example 2d: Using sodium hydroxide + additive + polyvinyl alcohol + ferric nitrate) The procedure and reactants are the same as in Example 2c, except that solution B is prepared by dissolving 30 g of ferric nitrate in 500 ml of water. The reaction temperature is 90° C. and the reaction time is varied. The results are shown in Table 2d below.
[0116] [Table 12]
[0117] Example 2e: Using ethanol as solvent + additive + ferric nitrate Following the procedure of Example 2a, solution A was prepared by dissolving 12 g of 1,3,5-benzenetricarboxylic acid in a mixture of ethanol-water in a 1:1 ratio (100 ml each), followed by adding 0.5 g of hydroxypropylmethylcellulose additive under continuous stirring. Solution B is prepared by dissolving 30 g of ferric nitrate in 500 ml of water. The substrate is a substrate with a basis weight of 33 GSM. The reaction temperature is maintained at 90° C., while the reaction time is varied. The effect of varying the reaction time on the loading percentage of the in situ synthesized MOF on the substrate was investigated. The results are shown in Table 2e below.
[0118] [Table 13]
[0119] B: Using pretreated substrates (Example 2f: Using ferric chloride without additives) Three parts of a first solution (Solution-A) are each prepared by dissolving 10.4 g of 1,3,5-benzenetricarboxylic acid in an aqueous basic medium of 10 g of sodium hydroxide in 250 ml of water. A substrate made of glass fiber and having a basis weight of 33 GSM is pretreated with 5% silica sol and exposed to air drying. This pretreated substrate is also divided into three equal parts. Each pretreated substrate material after drying is immersed / soaked in a respective portion of Solution A at room temperature and then exposed to air drying. Three parts of a second solution (Solution-B) are each prepared by dissolving 30 g of ferric chloride in 500 ml of water. Each substrate treated and pretreated with Solution A is then reacted individually with a respective portion of Solution B at a given temperature and time, followed by air drying. The substrate containing the in situ synthesized MOF is then washed with water to remove by-products formed during the reaction and exposed to air drying. One substrate portion is then treated with 5% silica sol to increase strength. The substrate portion is then activated. The amount of loading of in situ synthesized MOF on the substrate and the effect of time variation on the loading percentage are investigated. The results obtained are shown in Table 2f below.
[0120] [Table 14]
[0121] (Example 2g: Using ferrous chloride without additives) The procedure described in Example 2f is followed. Two parts of solution A are prepared by dissolving 50.25 g of 1,3,5-benzenetricarboxylic acid in a solution of 27 g of sodium hydroxide dissolved in 650 ml of water, respectively. Two parts of solution B are prepared by dissolving 12 g of ferrous chloride in 480 ml of water in each part, instead of ferric chloride. The pretreated substrate is also divided into two equal parts. The substrate comprises a basis weight of 33 GSM. The loading percentage of the MOFs synthesized in situ on the substrate and the effect of time variations on the loading percentage are investigated. The results obtained are shown in Table 2g below.
[0122] [Table 15]
[0123] Example 3: In situ synthesis of CAU-10H Two parts of solution A are prepared by dissolving 50 g of isophthalic acid in 250 ml of dimethylformamide as a solvent. A substrate with a basis weight of 33 GSM is pretreated with 5% silica sol and then naturally dried. This dried substrate is then also divided into two equal parts. Each part is then immersed in a respective part of solution A at room temperature and then naturally dried. Two parts of solution B are prepared by dissolving 100 g of aluminum sulfate in 500 ml of water. Each part of the substrate already immersed in solution A is then individually immersed in a respective part of solution B to initiate the reaction at 70° C. for different times and then naturally dried. The substrate is then washed with water to remove by-products formed during the reaction, exposed to natural drying and activated in a drying chamber at 140° C. for 2 hours. The percentage loading of the MOFs synthesized in situ on the substrate and the effect of time variation on the loading are investigated. The results are shown in Table 3 below.
[0124] [Table 16]
[0125] Example 4: In situ synthesis of COF-1: Solution-A is prepared by dissolving 2g of 1,4-benzenediboronic acid in a mixture of ethanol-water in a volume ratio of 1:3. 1.5g of xanthan gum is added followed by 10ml of silica sol under continuous stirring. Solution-B is prepared by mixing mesitylene and 1,4-dioxane in a volume ratio of 1:1. The reaction time is 2 hours and the reaction temperature is room temperature. The results are shown in Table 4 below. The FTIR peaks corresponding to BO with transmittance of 138.1%, BC with 1026.3% and B3O3 with 710.9% confirm the formation of COF-1 as shown in Figure 4b in comparison with available literature.
[0126] [Table 17]
[0127] Example 5: In situ synthesis of ZIF-1 The procedure of Example 4 is followed, except that solution A is prepared by dissolving 6 g of imidazole in 360 ml of DMF, and solution B is prepared by dissolving 4.05 g of zinc nitrate in 405 ml of dimethylformamide. The reaction time is 30 min and the reaction temperature is 70° C. The results are shown in Table 5 below. The representative XRD peak at 2θ position 23.39 corresponds to the maximum relative intensity as reported in the literature for ZIF-1. This is shown in FIG. 4c.
[0128] [Table 18]
[0129] (Example 6: Sequential immersion in solution A and solution B in any order) Example 6a The procedure of Example 1g is followed, except that the glass fiber substrate is not subjected to any pretreatment and the immersion order is first solution A followed by solution B. The results are shown in Table 6a below.
[0130] [Table 19]
[0131] Example 6b The procedure of Example 6a was followed, except that the immersion order included solution B followed by solution A. The results are shown in Table 6b below.
[0132] [Table 20]
[0133] Example 7: Co-synthesis of aluminum fumarate and CAU-10H Solution A1 is prepared by dissolving isophthalic acid in DMF. Solution A2 is prepared by adding potassium hydroxide in water followed by fumaric acid under continuous stirring. Equal amounts of both above solutions are mixed together to form a homogenous solution A. A glass fiber substrate is immersed in the above solutions at room temperature and then allowed to air dry. Solution B is prepared by dissolving aluminum sulfate in water. Then the glass fiber substrate already immersed in solution A is reacted with solution B at a given temperature and time and then air dried. Then the synthesized glass fiber is washed with water to remove the by-products formed during the reaction. Then it is air dried and activated in a drying chamber at 140°C for 2 hours. The process conditions, concentrations and results are shown in Table 7.
[0134] [Table 21]
[0135] Example 8: Co-synthesis of aluminum fumarate and aluminum silicate Solution-A is prepared by dissolving potassium hydroxide in water. Then fumaric acid is added to it with continuous stirring. Xanthan gum is added followed by sodium silicate and mixed well. The substrate is immersed in the above solution at room temperature and then allowed to dry naturally. Solution-B is prepared by dissolving aluminum sulfate in water. Then the substrate already immersed in solution-A is reacted with solution-B at a given temperature and time and then allowed to dry naturally. The synthesized substrate is washed with water to remove the by-products formed during the reaction. Then it is air-dried and activated in a drying chamber at 140°C for 2 hours. The details are given in Table 8.
[0136] [Table 22]
[0137] (Example 9: CROSS CO-SYNTHESIS: Cross co-synthesis of aluminum fumarate and MIL-100(Fe)) Solution-A1 is prepared by dissolving 1,3,5-benzenetricarboxylic acid in aqueous basic solvent i.e. sodium hydroxide in water with continuous stirring. Xanthan gum is also added as an additive. Solution-A2 is prepared by adding potassium hydroxide in water followed by fumaric acid with continuous stirring. Xanthan gum is also added as an additive. Both the above solutions are mixed together to form a homogeneous solution-A. Solution-B1 is prepared by dissolving ferrous chloride in water. Solution-B2 is prepared by dissolving aluminum sulfate in water. Equal amounts of both the above solutions are mixed together to form a homogeneous solution-B. A glass fiber substrate is immersed in solution-A at room temperature and then allowed to dry naturally. Then the glass fiber substrate already immersed in solution-A is reacted with solution-B at a given temperature and time and then allowed to dry naturally. Then the synthesized glass fiber is washed with water to remove the by-products formed during the reaction. It was then air dried and activated in a drying chamber at 140° C. for 2 hours. The results are shown in Table 9 below.
[0138] [Table 23]
[0139] Example 10: Fabrication of honeycomb matrix using in situ synthesized aluminum fumarate (shown in FIG. 8) Solution A is prepared by dissolving 18.1 kg of potassium hydroxide in 68 L of water followed by the addition of 15 kg of fumaric acid at a temperature in the range of 60° C. with continuous stirring. 300 g of viscosity increasing additive, xanthan gum, is added with continuous stirring. 5 L of polyvinyl alcohol is also added and mixed well. A glass fiber based substrate is immersed in solution A to form a honeycomb geometry. The substrate is then corrugated to form a rotor which is then immersed in an aluminum sulfate solution having a specific gravity of 1.20. The immersion time is 30 minutes and the immersion temperature is 45° C. The rotor is then dried, washed and dried again before being activated in a drying chamber. The results are shown in Table 10 below.
[0140] [Table 24]
[0141] Example 11: Fabrication of a honeycomb rotor, in which the substrate passes through a continuously formed mixture of components A and B, undergoing a simultaneous and in situ continuous synthesis process of the adsorbent, and then formed into a honeycomb substrate (as shown in FIG. 9). Solution A is prepared by dissolving 6.33 kg of sodium hydroxide in 53.75 L of water followed by the addition of 6.08 kg of fumaric acid at room temperature under continuous stirring. Solution B is prepared by dissolving 12.5 kg of aluminum sulfate in 50 L of water. Both solutions are mixed together at a temperature of 35° C. The substrate is continuously passed through this solution and transformed into a honeycomb shape to form a rotor. The rotor is then dried, washed and dried again before being activated in a drying chamber. The results are shown in Table 11 below.
[0142] [Table 25]
[0143] Example 12: Fabrication of a preformed honeycomb matrix with MOFs synthesized in situ (on and within the honeycomb porous substrate) according to one embodiment of the present invention (FIG. 10). A honeycomb matrix is prepared using glass fiber substrate and silica sol as hardener. Solution A is prepared by dissolving 18.1 kg of potassium hydroxide in 68 L of water followed by the addition of 15 kg of fumaric acid at a temperature in the range of 60° C. with continuous stirring. A viscosity increasing additive, 300 g of xanthan gum, is added with continuous stirring. 5 L of polyvinyl alcohol is also added and mixed well. Solution-B is an aluminum sulfate solution having a specific gravity of 1.20. The pretreated matrix is then immersed in solution-A at room temperature for 5 minutes, after which it is naturally dried and immersed in solution-B. The immersion time is 30 minutes and the immersion temperature is 45° C. The rotor is then dried, washed and dried again before being activated in a drying chamber. The results are as shown in Table 12 below.
[0144] [Table 26]
[0145] Example 13: Fabrication of a honeycomb matrix rotor by impregnating a substrate in a slurry of aluminum fumarate and forming it into a honeycomb rotor (as shown in FIG. 11). A slurry of aluminum fumarate is prepared by adding 20 kg of aluminum fumarate to 31.6 L of water under continuous stirring. 21 L of acid sol having a specific gravity of 1.12 when thoroughly mixed is added to it. Then 20 L of polyvinyl alcohol is added to the solution and mixed well until a homogenous solution is obtained. A glass fiber substrate is immersed in the slurry and then corrugated. The formed rotor is dried and then immersed in 5% silica sol. It is then dried and activated. The results are as shown in Table 13 below.
[0146] [Table 27]
[0147] Example 14: Pre-prepared honeycomb matrix rotor (shown in FIG. 12) impregnated by immersion in a slurry of aluminum fumarate. A slurry containing aluminum fumarate is prepared by adding 20 kg of aluminum fumarate to 31.6 L of water under continuous stirring. 21 L of acid sol having a specific gravity of 1.12 when mixed thoroughly is added to it. Then 20 L of polyvinyl alcohol is added to the solution and mixed well until a homogenous solution is obtained. A honeycomb matrix is prepared using a glass fiber substrate and silica sol as a hardener. The matrix is then immersed in the slurry. The formed rotor is dried and then activated in a drying chamber. The results are as shown in Table 14 below.
[0148] [Table 28]
Claims
1. 1. A method for in situ synthesis of MOFs, COFs or ZIFs on and within a porous substrate by contacting the porous substrate with a first solution and a second solution, the first and second solutions being capable of forming the MOFs, COFs or ZIFs.
2. The method of claim 1 , wherein the porous substrate is contacted with the first solution and the second solution sequentially in any order or simultaneously as a mixture of the two solutions.
3. 3. The method of claim 1 or 2, wherein the first solution and / or the second solution comprises a mixture of two or more solutions, and the resulting in situ synthesized sorbent is one or more MOFs, COFs, or ZIFs, or a combination of one or more of MOFs, COFs, or ZIFs with an inorganic sorbent.
4. 4. The method of claim 1, wherein the contacting is performed by immersion or soaking.
5. 5. The method of any one of claims 1 to 4, wherein the soaking / dipping time, temperature, pressure, concentration, and viscosity for both the first and second solutions are optimized with or without the use of enhancers or inhibitors.
6. 6. The method according to claim 1, wherein the mass ratio of the in situ synthesized adsorbent to the bare substrate is in the range of 0.1 to 6 times by mass of the adsorbent to the bare substrate, preferably in the range of 0.5 to 4 times by mass of the bare substrate, more preferably in the range of 1.5 to 3 times by mass of the bare substrate.
7. 7. The method of any one of claims 1 to 6, wherein the substrate is pretreated with a curing agent selected from the group consisting of silica sol, alumina sol, polyvinyl alcohol, polyvinyl acetate, acrylate, water glass, and any combination thereof.
8. 8. The method according to claim 1, wherein the substrate is washed, dried and activated after the in situ synthesis to remove unreacted or excess starting materials or by-products formed during the synthesis.
9. 9. The method of any one of claims 1 to 8, wherein the substrate is transformed into a desired geometric structure after immersion in a first solution, and then the shaped substrate is immersed / soaked into a second solution to form an adsorbent in situ.
10. 9. The method of any one of claims 1 to 8, wherein the substrate is first shaped into a desired geometric structure, and then the shaped substrate is sequentially immersed in a first solution and a second solution, or a mixture of the first and second solutions, to form an adsorbent in situ.
11. 11. The method of claim 1, wherein a dosage of titanium silicate is added to the first solution or the second solution prior to treating the substrate.
12. 12. The method of claim 1, wherein the substrate is subjected to burn-off of substantially all of the organic binding material without affecting the properties of the adsorbent.
13. 13. The method of any one of claims 1 to 12, wherein the in situ synthesized MOF comprises any one of MIL-100(Fe), AlF, MOF-5, Cu-BTC, MIL-53, MIL-68, Mg-MOF-74, MIL-101(Cr), MOF 801, MOF 177, CAU-10H, MOF 808, IR-MOF-8, CPO-Ni(27), MOF 199, DMOF(Zn), DUT-4, and combinations thereof.
14. 13. The method of any one of claims 1 to 12, wherein the COF formed in situ is selected from the group consisting of COF-202, COF-1, COF-5, PcPBBA, TpPa-1, TpPa-2, TpPa-NO2, TpPa-F4, TpBD, TpBD-(NO2), and combinations thereof.
15. The method of any one of claims 1 to 12, wherein the ZIF is selected from the group consisting of ZIF-1, ZIF-7, ZIF-8, ZIF-35, ZIF-67, ZIF-69, ZIF-71, ZIF-90, ZIF-95, and ZIF-100, and combinations thereof.
16. 16. The method of any one of claims 1 to 15, wherein the substrate is a porous substrate selected from the group consisting of glass fibers, ceramic fibers, natural fibers, synthetic fibers, biosoluble fibers, pulp, and any combination thereof, and is optionally reinforced with 2-8% by weight of a hardener selected from the group consisting of silica sol, alumina sol, polyvinyl alcohol, polyvinyl acetate, and acrylate.
17. 17. The method of any one of claims 1 to 16, wherein the filled substrate is dried at a temperature of up to 90°C.
18. The method according to any one of claims 1 to 17, wherein the substrate treated with both solutions is dried at a temperature in the range of 80°C to 160°C.
19. 19. The method of any one of claims 1 to 18, wherein 0.25 to 15% by weight of an additive selected from the group consisting of xanthan gum, sodium alginate, hydroxypropyl methylcellulose, guar gum, starch, and ethylene glycol is added to the substrate via a solution containing an organic component.
20. The organic linker used to impregnate the substrate is selected from the group consisting of oxalic acid, tartaric acid, succinic acid, 1,4-butanedicarboxylic acid, 1,4-butene-dicarboxylic acid, 4-oxopyran-2,6-dicarboxylic acid, decanedicarboxylic acid, 1,8-heptadecanedicarboxylic acid, 1,6-hexanedicarboxylic acid, heptadecanedicarboxylic acid, acetylenedicarboxylic acid, 1,9-heptadecanedicarboxylic acid, 1,2-benzenedicarboxylic acid, 1,3-benzenedicarboxylic acid, 2,3-pyridinecarboxylic acid, pyridine-2,3-dicarboxylic acid, 1,4-benzenedicarboxylic acid, p-benzenedicarboxylic acid, imidazole-2,4-dicarboxylic acid, 2-methylquinoline-3,4-dicarboxylic acid, Quinoline-2,4-dicarboxylic acid, quinoxaline-2,3-dicarboxylic acid, 6-chloroquinoxaline-2,3-dicarboxylic acid, 1,3-butadiene-1,4-dicarboxylic acid, 4,4'-diaminophenylmethane-3,3'-dicarboxylic acid, quinoline-3,4-dicarboxylic acid, diimidedicarboxylic acid, pyridine-2,6-dicarboxylic acid, 2-methylimidazole-4,5-dicarboxylic acid, 7-chloro-4-hydroxyquinoline-2,8-dicarboxylic acid, thiophene-3,4-dicarboxylic acid, tetrahydropyran-4,4-dicarboxylic acid, perylene-3,9-dicarboxylic acid, 2-isopropylimidazole-4,5-dicarboxylic acid, perylene dicarboxylic acid, Pluriol E 200-dicarboxylic acid, 3,5-cyclohexadiene-1,2-dicarboxylic acid, octanedicarboxylic acid, pentane-3,3-carboxylic acid, 3,6-dioxaoctanedicarboxylic acid, 4,4'-diamino-1,1'-biphenyl-3,3'-dicarboxylic acid, 4,4'-diaminobiphenyl-3,3'-dicarboxylic acid, benzidine-3,3'-dicarboxylic acid, 1,1'-binaphthyl dicarboxylic acid, 1,4-bis(phenylamino)benzene-2,5 -dicarboxylic acid, 7-chloro-8-methylquinoline-2,3-dicarboxylic acid, 1-anilinoanthraquinone-2,4'-dicarboxylic acid, 1,4-bis(carboxymethyl)piperazine-2,3-dicarboxylic acid, phenylindanedicarboxylic acid, 7-chloroquinoline-3,8-dicarboxylic acid, polytetrahydrofuran 250-dicarboxylic acid, 1-(4-carboxy)phenyl-3-(4-chloro)phenylpyrazoline-4,5-dicarboxylic acid, 1,4,5,6,7,7-Hexachloro-5-norbornene-2,3-dicarboxylic acid, 1,3-dibenzyl-2-oxoimidazolidine-4,5-dicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, naphthalene-1,8-dicarboxylic acid, 1,3-dibenzyl-2-oxoimidazolidine-4,5-cis-dicarboxylic acid, 2,2'-biquinoline-4,4'-dicarboxylic acid, 2-benzoylbenzene-1,3-dicarboxylic acid, pyridine-3,4 dicarboxylic acid, 3,6,9-trioxaundecane dicarboxylic acid, Pluriol E 300 dicarboxylic acid, Pluriol E 400 dicarboxylic acid, hydroxybenzophenone dicarboxylic acid, Pluriol E 600-dicarboxylic acid, pyrazole-3,4-dicarboxylic acid, bis(4-aminophenyl)sulfondiimide-dicarboxylic acid, 5,6-dimethyl-2,3-pyrazinedicarboxylic acid, bis(4-aminophenyl)etherdiimide-dicarboxylic acid, 2,3-pyrazinedicarboxylic acid, 4,4'-diaminodiphenylmethanediimide-dicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,3-adamantanedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 8-methoxy-2,3-naphthalenedicarboxylic acid, 8-sulfo-2,3-naphthalenedicarboxylic acid, anthracene-2,3-dicarboxylic acid, 8-nitro-2,3-naphthalenecarboxylic acid, 2',3'-diphenyl-p-terphenyl-4,4''-dica The method according to any one of claims 1 to 19, wherein the bidentate or tridentate ligand is selected from the group consisting of dicarboxylic acids such as carboxylic acid, (diphenyl ether)-4,4'-dicarboxylic acid, 4(1H)-oxothiochromene-2,8-dicarboxylic acid, imidazole-4,5-dicarboxylic acid, 5-tert-butyl-1,3-benzenedicarboxylic acid, 7,8-quinolinedicarboxylic acid, 4,5-imidazoledicarboxylic acid, 1,3,5-benzenetricarboxylic acid, and 1,3,5-tris(4-carboxyphenyl)benzene, and the heteroaromatic organic compound for in situ synthesis of ZIF is selected from the group consisting of imidazole, benzimidazole, chlorobenzimidazole, nitroimidazole, 2-methylimidazole, and imidazole-2-carboxaldehyde.
21. 21. The method of any one of claims 1 to 20, wherein the metal salt is selected from the group consisting of ferric nitrate, ferric chloride, ferrous chloride, chromium nitrate, chromium chloride, aluminum sulfate, aluminum chloride, aluminum bromide, aluminum hydrogen sulfate, aluminum dihydrogen phosphate, aluminum monohydrogen phosphate, aluminum phosphate, aluminum nitrate, nickel acetate, zirconium oxychloride, zinc nitrate, zinc acetate, copper acetate, copper nitrate, cobalt nitrate, and magnesium nitrate.
22. 22. The method of any one of claims 1 to 21, wherein the concentration of the metal salt in the solution ranges from 5% to 50% by weight of the solution.
23. 23. The process of any one of claims 1 to 22, wherein the solvent is selected from the group consisting of water, methanol, ethanol, n-propanol, iso-propanol, n-butanol, isobutanol, t-butanol, pentanol, hexanol, dimethylsulfoxide, N,N-dimethylformamide, N,N-diethylformamide, toluene, acetonitrile, dioxane, N,N-dimethylacetamide, benzene, chlorobenzene, tetrahydrofuran, ethyl acetate, methyl ethyl ketone, pyridine, sulfolane, glycols, N-methylpyrrolidone, diethylamine, triethylamine, gamma-butyrolactone, cyclohexanol, acetylacetonate, mesitylene, and other similar aqueous, non-aqueous, aliphatic, aromatic, organic, inorganic solvents, and mixtures thereof.
24. 24. The process according to any one of claims 1 to 23, wherein the reaction temperature is in the range of 5 to 120°C and the reaction time is in the range of 10 minutes to 24 hours.
25. In situ synthesis on and within substrates, gas separation membranes, dehumidification applications, drug delivery systems, energy storage devices, CO 2 Porous substrates with MOFs, COFs or ZIFs for use in capture, sensors and lithium batteries.
26. A sorbent matrix, in which one or more sorbents selected from the group consisting of MOFs, COFs, ZIFs, and combinations thereof with inorganic sorbents are synthesized in situ on and within the substrate.
27. An adsorbent matrix, in which one or more adsorbents selected from the group consisting of MOFs, COFs, ZIFs, and combinations thereof with inorganic adsorbents are impregnated on and within the substrate.
28. 28. The adsorbent matrix of claim 26 or 27, wherein the matrix is in the form of a honeycomb.
29. 29. An adsorbent matrix according to any one of claims 26 to 28, wherein the ratio of the adsorbent to the matrix is in the range of 0.1 to 6 times the mass of the adsorbent to the bare substrate, preferably in the range of 0.5 to 4 times the mass of the bare substrate, more preferably in the range of 1.5 to 3 times the mass of the bare substrate.
30. 30. The adsorbent matrix of any one of claims 26 to 29, wherein the MOF comprises any one of MIL-100(Fe), AlF, MOF-5, Cu-BTC, MIL-53, MIL-68, Mg-MOF-74, MIL-101(Cr), MOF 801, MOF 177, CAU-10H, MOF 808, IR-MOF-8, CPO-Ni(27), MOF 199, DMOF(Zn), DUT-4, and combinations thereof.
31. 30. The adsorbent matrix of any one of claims 26 to 29, wherein the COF is selected from the group consisting of COF-202, COF-1, COF-5, PcPBBA, TpPa-1, TpPa-2, TpPa-NO2, TpPa-F4, TpBD, TpBD-(NO2), and combinations thereof.
32. 30. The adsorbent matrix of any one of claims 26 to 29, wherein the ZIF is selected from the group consisting of ZIF-1, ZIF-7, ZIF-8, ZIF-35, ZIF-67, ZIF-69, ZIF-71, ZIF-90, ZIF-95, and ZIF-100, and combinations thereof.
33. 33. The adsorbent matrix of any one of claims 26 to 32, wherein the substrate is a porous substrate selected from the group consisting of glass fibers, ceramic fibers, natural fibers, synthetic fibers, biosoluble fibers, pulp, and any combination thereof, optionally reinforced with 2-8% by weight of a hardener selected from the group consisting of silica sol, alumina sol, polyvinyl alcohol, polyvinyl acetate, and acrylates.
34. 30. The adsorbent matrix of any one of claims 26 to 29, wherein the adsorbent is a combination of MOFs, COFs, or ZIFs, and an inorganic adsorbent.
35. 35. A method for producing an adsorbent matrix according to any one of claims 26 to 34, wherein one or more adsorbents selected from the group consisting of MOFs, COFs, ZIFs, combinations of one or more MOFs, COFs, ZIFs with inorganic adsorbents are in situ synthesized thereon or impregnated thereon.
36. 36. The method of claim 35, wherein the in situ synthesis or impregnation is followed by washing to remove unreacted or excess starting materials or by-products formed during the synthesis, drying, and / or activation.
37. 37. The method of claim 35 or 36, comprising immersing the substrate in a first solution and, after converting the immersed substrate into a shaped matrix, immersing the shaped matrix in a second solution to form in situ an adsorbent selected from the group consisting of MOFs, COFs, ZIFs, and combinations of one or more MOFs, COFs, ZIFs with inorganic adsorbents.
38. 38. The method of any one of claims 35 to 37, wherein the first solution or the second solution is a combination of two or more solutions.
39. 39. The method of any one of claims 35 to 38, wherein the steps of contacting with the first and second solutions can be sequential in any order or simultaneous with a mixture of the first and second solutions.
40. 40. The method of any one of claims 35 to 39, wherein the adsorbent substrate is treated with a curing agent.
41. 36. The method of claim 35, wherein the adsorbent is present in the form of a slurry, and optionally the impregnation is carried out using a suitable binder selected from the group consisting of inorganic or organic binders.
42. 41. The method of any one of claims 35 to 40, wherein the soaking / dipping time and concentration / viscosity for the adsorbent slurry during impregnation are optimized.
43. A method for filtering adsorbates from a fluid using a sorbent-containing matrix comprising a sorbent selected from one or more of MOFs, COFs, ZIFs, and a combination of an inorganic sorbent provided thereon.
44. 44. The method of claim 43, wherein the fluid may be a liquid or a gas, or a combination of liquids or a combination of gases.
45. 45. A method according to claim 43 or 44, wherein the adsorbate may be a liquid or a gas, or a combination of liquids or a combination of gases.
46. The adsorbate is water vapor, CO 2 , VOCs, and other gaseous substances, and the adsorbent-containing matrix is provided in a desiccant / adsorbent forming wheel, or a formed matrix of any geometric shape.
47. A desiccant wheel having an adsorbent matrix comprising an adsorbent selected from the group consisting of MOFs, COFs, ZIFs, hybrids of one or more MOFs, COFs, ZIFs with inorganic adsorbents, and any combination thereof provided thereon.
48. 48. The desiccant wheel of claim 47, wherein the adsorbent is synthesized in situ on and within the matrix or the adsorbent is impregnated into the matrix.
Citation Information
Patent Citations
Chemical substance adsorbing material and its preparation
JP1997290151A
Adsorbent for gas and its preparing method
JP2001137703A
Monolithic materials for gas storage
JP2010500159A
Adsorption sheet and adsorption element using the same
JP2013154301A
Adsorption sheet
JP2013154302A